PERBANDINGAN HASIL BELAJAR EKONOMI DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DAN TGT - Lisna Sari; Nurdin Nurdin; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2015)
The background of this research is the result of studying economics which still relatively low. The objective of the research was to know the differences result of learning economics at the tenth grade social studies of SMAN 13 Bandar Lampung and which the model that is more effective between the cooperative learning model of TAI and TGT. The population on this research were 160 students and 79 students as sample (2 class) taken by using cluster random sampling technique. The design of this research was pretest-posttest only control design. The collection of data through observation, interview, documentation and test. The data analysis technique used t-test polled varians and effectiveness of N-Gain. The result of the research showed: (1) There is the differences in the result of studying economics which used cooperative learning model of TAI and TGT and (2) The cooperative learning model of TAI is more effective than TGT.Latar belakang penelitian ini adalah hasil belajar Ekonomi yang masih tergolong rendah. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan hasil belajar Ekonomi pada siswa kelas X IPS SMAN 13 Bandar Lampung dan model mana yang lebih efektif antara model pembelajaran kooperatif tipe TAI dan TGT. Populasi dalam penelitian ini adalah 160 siswa dan sampel 79 siswa (2 kelas) diambil dengan menggunakan teknik cluster random sampling. Desain penelitian ini adalah pretest-posttest only control design. Pengumpulan data melalui wawancara, observasi, dokumentasi, dan tes. Teknik analisis data menggunakan t-test polled varians dan efektivitas N-Gain. Hasil penelitian menunjukkan: (1) Ada perbedaan hasil belajar Ekonomi siswa yang pembelajarannya menggunakan model pembelajaran kooperatif tipe TAI dan TGT dan (2) Model pembelajaran kooperatif tipe TAI lebih efektif dibandingkan TGT.Kata kunci : hasil belajar, TAI, TGT.